An in-situ Raman study on the oxidation of mackinawite as a corrosion product layer formed on mild steel in marginally sour environments. (1st August 2021) - Zhang, Wei; Young, David; Brown, Bruce; Shafer, Cody; Lu, Fei; Anyanwu, Ezechukwu; Singer, Marc
Highlights: Observed mackinawite layer in marginally sour environments by in situ Raman flow loop with flow cell. The mackinawite layer was oxidized by [O2 ](aq) > 3 ppb(w) and initiated pitting corrosion. The chemisorption FeS layer was detected by ex situ Raman microscopy. Abstract: An in situ Raman flow loop with flow cell was developed to enable observation of the mackinawite corrosion product layer generated in marginally sour environments with traces of oxygen ingress. As a result, the mackinawite corrosion product layer was found to be oxidized into magnetite in the solution when [O2 ](aq) > 3 ppb(w), which was linked to the pitting initiation of mild steel (API X65) in marginally sour environments. The 2D precursor of nano-crystal mackinawite, the chemisorption FeS layer, Sads (Fe), was detected by ex situ Raman microscopy.